Surgical management of the rheumatoid hand and wrist. Issue 1 (February 2019) - Wu, Feiran; Talwalkar, Sumedh
Abstract: Management of the patient with rheumatoid arthritis of the hand and wrist demands a methodical approach. Multidisciplinary assessment and treatment in conjunction with a rheumatologist and dedicated hand therapist are essential. Initial treatment should be conservative. However, when patients develop severe deformities refractory to medical treatment, or there is impending tendon rupture or nerve compression, surgical intervention is required. This article aims to provide a current review of the principles and common conditions in surgery for rheumatoid arthritis of the hand and wrist.